Two new species of moth flies (Diptera, Psychodidae) from the semi-arid region of Brazil - Bravo, Freddy; Araújo, Maíra Xavier (Zootaxa, 2013)
Two new species of Psychodinae, Psychodidae, from the semi-arid region of Brazil are described and illustrated: Arisemus rubeni sp. nov. and Lepidiella olgae sp. nov. Only nine psychodid species were previously known from that region.